Gentherapien für neuromuskuläre Erkrankungen - Saffari, Afshin; Weiler, Markus; Hoffmann, Georg F.; Ziegler, Andreas (Der Nervenarzt, 2019)
BackgroundFor a long time the treatment of neuromuscular diseases was considered to be purely symptomatic. Due to new technologies in recent years novel causal forms of treatment could be developed. Gene therapies for spinal muscular atrophy, Duchenne muscular dystrophy, limb-girdle muscular dystrophy, myotubular myopathy and hereditary motor and sensory neuropathy type 1A are currently being evaluated in clinical trials. Initial preliminary results are promising and the first preparation onasemnogene abeparvovec-xioi (Zolgensma®) for the treatment of spinal muscular atrophy has recently been approved by the U.S. Food and Drug Administration (FDA).ObjectiveThis review describes the principles of gene therapy, summarizes the interim results published so far and provides an overview of currently active or soon to be initiated gene therapy trials.ConclusionGene therapies have the potential to significantly influence the course of neuromuscular diseases. First positive intermediate results have been published and the first treatment has recently been approved in the USA. Long-term data on sustained effects and toxicity of gene therapies are not yet available. These novel treatment options will present new challenges for the healthcare systems concerning diagnosis, treatment and reimbursement.
Gesehen am 21.10.2019